Sex differences in elbow and wrist joint loading during the cartwheel and round off with different hand positions performed by young gymnasts. Issue 13 (3rd July 2019) - Farana, Roman; Strutzenberger, Gerda; Exell, Timothy; Skypala, Jiri; Wiltshire, Huw; Irwin, Gareth
ABSTRACT: The aim of the study was to determine if sex differences exist in the key elbow and wrist joint injury risk factors during different cartwheel (CW) and round-off (RO) techniques performed by young male and female artistic gymnasts. Sixteen active young gymnasts (8 males and 8 females) performed 30 successful trials of CW and RO with three different hand positions (parallel (10), T-shape (10) and reverse (10)). Synchronised kinematic and kinetic data were collected for each trial. Two-way repeated measures ANOVA (3 × 2, technique × sex) and effect-sizes (ES) were used for statistical analysis. In conclusion, female gymnasts exhibited greater normalised peak vertical ground reaction forces (VGRF), elbow and wrist compression forces and elbow internal adduction moments during CW and RO skills compared with male gymnasts. In both sexes, the parallel and reverse techniques increased peak VGRF, elbow and wrist compression forces and the elbow internal adduction moment. Increased elbow flexion resulted in decreased peak VGRF, elbow compression forces and elbow internal adduction moment. Injury risk factors including elbow extension and internal adduction moment with axial compression force suggest that a CW and RO in reverse and parallel techniques can be hazardous especially for young female gymnasts.